2019
DOI: 10.3855/jidc.11213
|View full text |Cite
|
Sign up to set email alerts
|

A Extensively drug-resistant Pseudomonas putida bacteremia that was resolved spontaneously

Abstract: Pseudomonas putida (P. putida) is a rare pathogen that causes various infections in newborns, neutropenic and cancer patients, or in patients with risk factors leading to immunosuppresion. Antibiotic resistance in P. putida is seen in growing numbers. Although it is less virulent compared to Pseudomonas aeruginosa, mortal infections are reported. Here, a P. putida case after an invasive procedure in a patient with gastrointestinal malignancy is reported. Although, it caused an antibiotic resistant bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Infections by other Pseudomonas species with an environmental origin and biotechnological potential, as Pseudomonas putida [ 112 , 113 , 114 , 115 ], have also been reported, although their prevalence is much lower. Besides intrinsic resistance determinants [ 116 , 117 ], the acquisition of carbapenemases, as KPC-2 [ 113 ], constitutes an additional risk for the efficient treatment of infections by these pathogens.…”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%
“…Infections by other Pseudomonas species with an environmental origin and biotechnological potential, as Pseudomonas putida [ 112 , 113 , 114 , 115 ], have also been reported, although their prevalence is much lower. Besides intrinsic resistance determinants [ 116 , 117 ], the acquisition of carbapenemases, as KPC-2 [ 113 ], constitutes an additional risk for the efficient treatment of infections by these pathogens.…”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%
“…The bacterial isolates were positive for oxidase, catalase, and growth at 42ºC, while the negative result for the indole test, methyl red test, methyl red -voges proskauer (MR-VP) test, gram stain, citrate utilization, and urease test. [26][27][28] The PCR product from the P.aeruginosa isolates was sequenced by DNA sequencer, and the sequence data compared using the BLAST program in NCBI, by which the PASS primers of 16S rDNA was aligned. The sequence analysis of these isolates showed strong similarities with the representative isolates that were retrieved from the NCBI database, and also determined the phylogenetic affiliation, based on nucleotide homology and phylogenetic analysis.…”
Section: Distribution Of Pseudomonas Spp According To Sexmentioning
confidence: 99%
“…However, there are numerous reports of wound and eye infections, bacteremia, urinary tract infection, central venous catheter infection, pneumonia, and soft tissue infections caused by P. putida. [4][5][6][7][8] P. luteola may cause infections of the bloodstream associated with pancreatitis, intravenous indwelling catheters, prosthetic valve endocarditic, foreign bodies, and coetaneous abscesses. Infrequently, non-bacteremia cases have been RESEARCH ARTICLE reported as post neurosurgical infections, fatal meningitis, appendicitis, or peritoneal dialysis catheters femur abscess, endophthalmitis, facial cellulite, leg ulcer in a patient with the sickle disease, peritonitis complicating, subphrenic abscess, and hand infection.…”
Section: Introductionmentioning
confidence: 99%
“…Although this microbial agent causes infections in cancer and immunosuppressed patients and is less virulent than Pseudomonas aeruginosa , fatal diseases have been reported. [4,5]…”
Section: Introductionmentioning
confidence: 99%
“…Although this microbial agent causes infections in cancer and immunosuppressed patients and is less virulent than Pseudomonas aeruginosa, fatal diseases have been reported. [4,5] P. putida infections used to be known to have a good prognosis. However, recent studies reported a high mortality rate (40%), particularly in patients with comorbid conditions, [5,6] attracting the attention of clinicians.…”
Section: Introductionmentioning
confidence: 99%